ENT 530 Social Media Portfolio / Fatin Liyana Abdul Rahim - Abdul Rahim, Fatin Liyana
Jeruk Asam Boi Kecur Liuq is a product that being produced homemade by the owner of the business, which is by me. The main purpose of this product is to be enjoying during leisure time. The simple food that the customer could eat without have to use a lot of energy. The target market for this product is for student UiTM Puncak Alam. The business is based on sole proprietorship business ownership, where all the profit and loss will be bear by me alone. The method of selling in this business is using cash on delivery. The customer that interested need to order first before the product could be made because I want to maintain the quality of the product and sell only fresh product. My dream for this product and business could got its own place at everyone mind and heart. I also hope the business will be operated smoothly without have to face any problem.